Known-Group Validity and Sensitivity to Change in the Sensory-Motor Dysfunction Questionnaire in Individuals with Neck Pain: A Pilot Study - Ushani Ambalavanar; Megan McIntosh; Heidi Haavik; Bernadette Murphy (Brain Sciences)
Background/Objectives: Sensorimotor dysfunction is often reported in individuals experiencing neck pain, irrespective of severity and chronicity. The treatment of neck dysfunction has been found to positively impact sensorimotor integration (SMI), thereby improving sensorimotor function. However, no patient-reported outcome measure has been validated for discrimination between healthy individuals and neck pain patients with disordered SMI, nor has there been documentation of positive change in SMI following neck pain treatment.The purpose of this study was to administer the Sensory-Motor Dysfunction Questionnaire (SMD-Q), for the purposes of: (1) known-group validity between individuals without and with chronic neck pain (CNP) or subclinical neck pain (SCNP); (2) assess the questionnaire’s capacity to quantify changes in altered SMI following a tailored treatment plan. Methods: Part 1—Known Group Validity: The SMD-Q was administered to 30 neck pain (13 with CNP, and 17 with SCNP), and 30 healthy participants. Part 2—Sensitivity to Change: The SMD-Q was re-administered to neck pain participants following their tailored treatment plans (SCNP—8-weeks and CNP—12 weeks). Results: The SMD-Q can discriminate between healthy and neck pain participants (p ≤ 0.001), and may be sensitive to showing treatment effects (ηp2 = 0.162; large effect size (ES)), but the sample size was too small to determine if it can discriminate treatment effects between groups (ηp2 = 0.070; medium ES). Conclusions: Differing degrees of disordered SMI can be discriminated by the SMD-Q, but further research is needed to determine its sensitivity to treatment.